2020
DOI: 10.3389/fpls.2020.586140
|View full text |Cite
|
Sign up to set email alerts
|

Red Light Controls Adventitious Root Regeneration by Modulating Hormone Homeostasis in Picea abies Seedlings

Abstract: Vegetative propagation relies on the capacity of plants to regenerate de novo adventitious roots (ARs), a quantitative trait controlled by the interaction of endogenous factors, such as hormones and environmental cues among which light plays a central role. However, the physiological and molecular components mediating light cues during AR initiation (ARI) remain largely elusive. Here, we explored the role of red light (RL) on ARI in de-rooted Norway spruce seedlings. We combined investigation of hormone metabo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 65 publications
6
19
0
2
Order By: Relevance
“…The induction and outgrowth of ARs are complex processes regulated by phytohormones, among which are JA, ETH and AUX (Gutierrez et al, 2012; Verstraeten et al, 2014; Steffens & Rasmussen, 2016; Lakehal & Bellini, 2019; Lakehal et al, 2019; Alallaq et al, 2020; Lakehal et al, 2020). The potential involvement of these phytohormones in AR spacing of c4h mutants was investigated using corresponding signalling mutants, namely coi1‐21 (JA), e tr1‐3 (ETH) and tir1afb2afb3 (AUX).…”
Section: Resultsmentioning
confidence: 99%
“…The induction and outgrowth of ARs are complex processes regulated by phytohormones, among which are JA, ETH and AUX (Gutierrez et al, 2012; Verstraeten et al, 2014; Steffens & Rasmussen, 2016; Lakehal & Bellini, 2019; Lakehal et al, 2019; Alallaq et al, 2020; Lakehal et al, 2020). The potential involvement of these phytohormones in AR spacing of c4h mutants was investigated using corresponding signalling mutants, namely coi1‐21 (JA), e tr1‐3 (ETH) and tir1afb2afb3 (AUX).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, far-red treated Eucalyptus globulus plants presented an increased carbohydrate content and rooted better ( Ruedell et al, 2015 ). In spruce, constant red light had a positive effect on rooting initiation of de-rooted seedlings, possibly by repressing the accumulation of the negative regulators jasmonate and cytokinins ( Alallaq et al, 2020 ). In eastern cottonwood ( P. deltoides ), the rooting of microcuttings grown in media with exogenous auxin (IBA), was better under fluorescent light than under light emitting diodes (LEDs) ( Hoffman et al, 2016 ).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The negative role of CKs in adventitious rooting has also been confirmed in many plant species that rely on vegetative propagation ( Lakehal and Bellini, 2019 ). For example, exogenous application of CK can inhibit AR formation in Malus domestica (apple) and Picea abies (Norway spruce) cuttings ( Mao et al , 2019 ; Alallaq et al , 2020 ). Similarly, Ramírez-Carvajal et al (2009) found that overexpressing an active variant of type-B cytokinin RESPONSE REGULATOR 13 ( PtRR13 ) delayed AR formation in Populus tremula×Populus alba stem cuttings.…”
Section: Discussionmentioning
confidence: 99%